Physiology, Pathophysiology and Clinical Relevance of D-Amino Acids Dynamics: From Neurochemistry to Pharmacotherapy - Garcia Huidobro-Toro, J; Eugenin-Leon, J; Donoso-Gomien, M; Pulgar-Sepulveda, R (John Wiley and Sons Inc, 2024)
Over three decades ago, two independent groups of investigators identified free D-aspartic and later D-serine in specific brain nuclei and endocrine glands. This finding revealed a novel, non-proteinogenic role of these molecules. Moreover, the finding that aged proteins from the human eye crystallin, teeth, bone, blood vessels or the brain incorporate D-aspartic acids to specific primary protein sequences fostered the hypothesis that aging might be related to D-amino acid isomerization of body proteins. The experimental confirmation that schizophrenia and neurodegenerative diseases modify plasma free D-amino acids or tissue levelsnurtured the opportunity of using D-amino acids as therapeutic agents for several disease treatments, a strategy that prompted the successful current application of D-amino acids to human medicine. © 2024 The Chemical Society of Japan and Wiley-VCH GmbH.